Understanding the need of Geriatric Medicine in Pakistan - Saema Tehseen, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the common problems of advancing age and their plausible solutions. Study design: Prospective Observational Study. Setting: Pakistan Airforce Hospital Sargodha Duration of study: One year from 1st January 2020 till 31st December 2020. Methods: All elderly citizens both male and female were interviewed regarding the common difficulties faced by them in their day to day life to quantify the magnitude of the problem and consequently help finding easy plausible solutions . Results: All senior citizens approachable in person or on phone over the age of sixty five both males and females were interviewed. Interviews were carried out by using a specially designed short , crisp and easy to understand questionnaire. Common difficulties faced in this age group were listed and their magnitude was estimated so that strategies can be defined to help resolve those. Common difficulties were related to social life, relationships, self care , mobility, psychological and emotional health. In the wake of interviews we found majority of people highlighted that with advancing age the quality of care imparted to them diminishes although the demands made are minimized due to lack of reassurance and uncertainty. This instills a lack of confidence in them. Moreover the monotony over days, weeks and years causes a loss of self worth and self esteem. Conclusion: As an evolving society of a developed country we have the advantage of utilizing models of Geriatric Care already in place in the developed world. Whereby Geriatric Medicine is a specialty for addressing the needs of advancing age and Hospice looks after the terminally ill patients of any age in a nonhospital environment. Many solutions can be offered and exercised without a big resource may it be human, material or financial.